Diagnostic aid tests and conflicts of interest in our hospitals: Masked corruption? - León-Jiménez, Franco Ernesto (2022)
In public hospitals, the difficulties arising from the lack of logistical resources in the clinical laboratory make quality care even more difficult. The lack of management by processes and the conflicts of interest arising from the proliferation of laboratories that are not certified or accredited make a new vision on this subject necessary. Evidence-Based Laboratory Medicine is a tool from which clinicians, technologists and biologists can benefit. On the other hand, it is necessary that, from the state, the efforts made by the UNAGESP, IETSI, SIS, INACAL, SUSALUD, the Ombudsman's Office, the Comptroller General's Office of the Republic, professional associations and private companies to improve the management of the clinical laboratory be agreed upon.